Evaluation of relative impact of aerosols on photovoltaic cells through combined Shannon's entropy and Data Envelopment Analysis (DEA). (May 2017) - Ghosh, Santosh; Yadav, Vinod Kumar; Mukherjee, Vivekananda; Yadav, Pankaj
Abstract: One of the biggest challenge before the world today is to find a trade-off between high energy demand and mitigation of greenhouse gas emissions. Researchers and energy policy makers around the world are now resorting to renewable energy (RE), as a solution to this crisis with special focus on solar energy, as it is the most abundantly available RE source. However, the requirement of high upfront capital investment is an inhibiting factor behind seamless deployment of solar energy technologies. Hence it is of paramount importance to increase the techno-commercial viability of the projects by leveraging on the environmental factors specific to project sites. In the present work, the impact of different kind of aerosols, which characterize different distinct geographical regions, on the performance of Photovoltaic (PV) cells have been investigated experimentally under different irradiation levels. The complex set of data generated by the experiment has been analysed and indexed by application of combined Shannon's entropy and Data Envelopment Analysis (DEA) to quantify the relative performance of the system under different environmental conditions, different TSPs at their different concentration levels. Through this work a comprehensive approach is proposed for the decision makers to enhance the techno-commercial viability of the PV projects. Highlights: Experimental study of PV cells under different dusts types, weights & irradiance. Primary data presented in terms of I-V, P-V curves for all the scenarios. Analysis of data by combined Shannon's entropy and DEA method for deeper insight. Sand found to be best and ash worst for PV performance in Indian environment. Approach to identify most favourable geographical location for PV site proposed.